2017
DOI: 10.1111/bpa.12452
|View full text |Cite
|
Sign up to set email alerts
|

Impaired oligodendroglial turnover is associated with myelin pathology in focal cortical dysplasia and tuberous sclerosis complex

Abstract: Conventional antiepileptic drugs suppress the excessive firing of neurons during seizures. In drug‐resistant patients, treatment failure indicates an alternative important epileptogenic trigger. Two epilepsy‐associated pathologies show myelin deficiencies in seizure‐related brain regions: Focal Cortical Dysplasia IIB (FCD) and cortical tubers in Tuberous Sclerosis Complex (TSC). Studies uncovering white matter‐pathology mechanisms are therefore urgently needed to gain more insight into epileptogenesis, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 50 publications
5
73
0
Order By: Relevance
“…Copy number variations in SMO a receptor in the Shh pathway have been recently shown in hypothalamic hamartoma associated with gelastic seizures and DEPDC5 and NPRL3 mutations reported in FCDII . Further histological features in common between MVNT and FCD IIB include the striking hypomyelination of involved white matter which may relate to deficiencies in oligodendroglial lineages . Also the distinctive MCM2 positivity of VC is reminiscent of balloon cells in FCD .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Copy number variations in SMO a receptor in the Shh pathway have been recently shown in hypothalamic hamartoma associated with gelastic seizures and DEPDC5 and NPRL3 mutations reported in FCDII . Further histological features in common between MVNT and FCD IIB include the striking hypomyelination of involved white matter which may relate to deficiencies in oligodendroglial lineages . Also the distinctive MCM2 positivity of VC is reminiscent of balloon cells in FCD .…”
Section: Discussionmentioning
confidence: 92%
“…L. SMI94 for myelin basic protein, as well as demonstrating the diminished myelination in the white matter nodules (see also Figure 2), also showed membranous labelling of the VC (arrow). Bar 3 histological features in common between MVNT and FCD IIB include the striking hypomyelination of involved white matter which may relate to deficiencies in oligodendroglial lineages (46,51,55,70). Also the distinctive MCM2 positivity of VC is reminiscent of balloon cells in FCD (61).…”
Section: Neoplasia or Malformationmentioning
confidence: 99%
“…Interestingly, in the experimental model synaptic transmission is abolished during a P‐type seizure (but not at its onset), possibly because of potassium‐induced fiber depolarization; in principle, this hypothesis could be verified in patients with an appropriate, ethically approved protocol designed for testing the response to low‐amplitude local stimulation of the EZ during P‐type seizures. The ictogenic mechanism proposed for P‐type seizures in the experimental animal model may be relevant to explain seizure generation in focal cortical dysplasia type IIb and in the cortex of TLE patients with and without associated dysplasia, where unmyelinated fibers in the subcortical white matter are pathologically augmented.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hamilton and Nesbit 5 did not identify FCD I in their case of oligodendroglial hyperplasia, the authors suggested that this could be the mildest end of the spectrum of a neuronal migrational disorder or microdysgenesis. In a recent study, Scholl et al19 also identified oligodendroglial hyperplasia in malformations of cortical development, with the exception of FCD IIb and cortical tubers.…”
mentioning
confidence: 93%